Prevalence of C282Y and H63D mutations in the HFEgene in patients from São Paulo and Southern Brazil - Marcos E. Herkenhoff; Ana Kelly Pitlovanciv; Vanessa R. Remualdo (Sociedade Brasileira de Patologia Clínica, 2016)
ABSTRACT Hereditary hemochromatosis (HH) is an autosomal recessive disorder caused by mutations in the HFE gene; it is characterized by the risk of iron overload. C282Y and H63D are the most associated mutations in HH. This study aimed to determine the frequency of mutations in the south of Brazil and São Paulo. It used the real-time polymerase chain reaction (PCR) technique and the results collected from Genolab data. In 90 individuals, 46.67% had at least one of the mutations for HH. There is a high prevalence of these mutations in both populations, therefore searching for patients under clinical suspicion is recommended.